2022
DOI: 10.1108/jed-09-2021-0144
|View full text |Cite
|
Sign up to set email alerts
|

Monetary policies and bank lending in developing countries: evidence from Sub-Sahara Africa

Abstract: PurposeThe purpose of this paper is to examine monetary policies and bank lending in the emerging economies of Sub-Sahara Africa.Design/methodology/approachThe dynamic system-generalized method of moments (GMM) that overcomes issues of unobserved period and country-specific effects, as well as potential endogeneity of explanatory variables, is applied in the estimation exercise. The study uses the data for 80 banks across 20 Sub-Saharan African countries from 2010 to 2019.FindingsThe findings show that expansi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Nonetheless, in lieu of the spread of various solutions, such as inspiring cultural values for entrepreneurship (Calza et al , 2020), encouraging locus of control and the desire for achievement (Uysal et al , 2022; Suyunov, 2021) and reducing entrepreneurial barriers (DÖLarslan et al , 2020; Abaidoo and Agyapong, 2022), we recommend a focus on entrepreneurial education and training, as this strategy focus will not only help to increase social entrepreneurial career interests and intentions but also help students to increase their social self-confidence related to establishing and managing social business ventures and help them to recognize social entrepreneurial opportunities in business markets. However, it is observed that this strategy also takes into consideration the pedagogical method of experiential learning, real-life business situations (Cui and Bell, 2022; Modugu and Dempere, 2022) and extracurricular activities (Nguyen et al , 2021). This can equip students with the necessary knowledge and ability in real-life entrepreneurship and help them to behave in accordance with their entrepreneurial intention.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, in lieu of the spread of various solutions, such as inspiring cultural values for entrepreneurship (Calza et al , 2020), encouraging locus of control and the desire for achievement (Uysal et al , 2022; Suyunov, 2021) and reducing entrepreneurial barriers (DÖLarslan et al , 2020; Abaidoo and Agyapong, 2022), we recommend a focus on entrepreneurial education and training, as this strategy focus will not only help to increase social entrepreneurial career interests and intentions but also help students to increase their social self-confidence related to establishing and managing social business ventures and help them to recognize social entrepreneurial opportunities in business markets. However, it is observed that this strategy also takes into consideration the pedagogical method of experiential learning, real-life business situations (Cui and Bell, 2022; Modugu and Dempere, 2022) and extracurricular activities (Nguyen et al , 2021). This can equip students with the necessary knowledge and ability in real-life entrepreneurship and help them to behave in accordance with their entrepreneurial intention.…”
Section: Discussionmentioning
confidence: 99%
“…The empirical review related to this study was mostly on Nigeria and is more on the effect of monetary policy on bank lending Modugu and Dempere (2022), Bala, Godiya, Hadith, and Maijama'a (2022), Adetutu et al, (2021), Olofinlade and Azeez (2021) Yunusa, Williams, and Adegbenle (2020), Lartey (2018), Abere, Obarafo, and Adewole (2020) Mukolu and Adeleke (2020), Olofinlade, Oloyede, and Oke (2020) and Mordi, et al (2019). Also, on the effect on bank credit especially to the private sector Awoniyi and Ogundipe (2021) 2018) Oyeyemi (2019).…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Also, on the effect on bank credit especially to the private sector Awoniyi and Ogundipe (2021) 2018) Oyeyemi (2019). There were just a few on cross-section, such as Modugu and Dempere (2022), Onyi and Umoh (2022), Takyi and Fosu (2019), Gambacorta (2017) and Balogun (2007). It is the study done by Balogun (2007) that is close to this study.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The upward trajectory in terms of money supply for most African countries caused domestic credit expansion for these countries which in turn leads to the depletion of their trade balances (Modugu & Dempere, 2022).…”
Section: Descriptive Statisticsmentioning
confidence: 99%